Reaksi Hipersensitif Daun Tembakau oleh Isolat Bakteri Pelarut Kalium pada Praformulasi Pupuk Hayati - Diyan Herdiyantoro; Mieke Rochimi Setiawati; Tualar Simarmata (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2022)
The fruitfulness of biofertilizer application in increasing plant growth and yield is when the formulation uses selected microbial isolates that do not cause disease to plants. Hypersensitivity test is carried out to ensure that the microbial isolates used in the formulation of biofertilizer are not pathogenic to plants. The purpose of this study was to determine the pathogenicity of three selected potassium solubilizing bacteria (KSB) isolates (BPK-DHJ3-3150[17], BPK-DHJ1-4125[2], and BPKDHJ2-5250[16]) isolated from the maize plant rhizosphere on Inceptisols Jatinangor. The research was conducted using a qualitative experimental method that obtained data in the form of visual photos. The three selected KSB isolates were inoculated on tobacco leaves and observed for necrosis symptoms. The experimental results showed that the three selected KSB isolates did not cause a positive hypersensitivity reaction in tobacco leaves, which was indicated by the absence of necrosis symptoms at the leaf location where the KSB isolates were inoculated. The three KSB isolates were nonpathogenic isolates to plants.